The Typology of V2 and the Distribution of Pleonastic die in the Ghent Dialect - De Clercq, Karen; Haegeman, Liliane (Frontiers in Psychology, 2018)
The goal of our paper is to provide a description of an apparent V3 pattern which is salient with some speakers of the Ghent dialect and is illustrated in (1), from Vanacker (1980). In such examples, what would be an initial adverbial constituent in the root clause vroeger (‘formerly’) is separated from the finite verb by what Vanacker (1980) labels a ‘pleonastic’ element, die, in effect leading to a superficial V3 order. At first sight, this element die is optional and it has no impact on the truth conditions of the proposition that it introduces. (2) is also acceptable in the dialect. (1) Vroeger, die bakten wij vier soorten brood formerly die baked we four sorts bread ‘We used to bake four kinds of bread.’ (Gijzenzele 0.28) (Vanacker 1980: 76) (2) Vroeger bakten wij vier soorten brood. formerly baked we four sorts bread ‘We used to bake four kinds of bread.’ In the first part of the paper, we will provide a description of the distribution of die. We will also compare its distribution with that of the more widely distribution resumptive adverbs dan (‘then’) and daar (‘there), which are typical of the Germanic V2 languages (Salvesen 2016). Our account will be based both on authentic data drawn from corpora and from anecdotal observations as well as on the results of elicitations with 10 native speakers of the dialect. In the second part of the paper we provide an analysis in terms of Wolfe’s (2016) typology of the syntax of V2. Adopting the articulated structure of CP as elaborated in the cartographic framework, we will propose that die is an overt spell out of the head Force and as such a root complementiser.